Physical Properties of Copper(II) Soap Complexes in Binary Solvent Mixture - Heda, L.C.; Mathur, Neha; Saxena, Pooja; Ahmed, Imran (Asian Journal of Chemistry, 2010)
Copper(II) soap complexes were synthesized with the N-donar ligands viz., benzothiazole and phenyl thiourea derived from p-methoxy aniline. These complexes were characterized by elemental analysis, molecular weight, melting point, IR, NMR and ESR spectral studies. In the present study, the solute-solvent interaction was investigated by density, molar volume and apparent molar volume measurements of different copper soap complexes in benzene-methanol mixtures. The critical micelle concentration were found to decrease with increase in average molecular weight of the soap complex. The apparent molar volume was examined in terms of masson equation. The limiting apparent molar volume (φv) was interpreted in terms of solute-solvent interaction while limiting slope (Sv) in terms of solute-solute interaction. The studies of various interactions suggest that solute-solvent interaction increases with the increase in carbon composition of fatty acid and lowering of molecular weight where as solute-solute interaction decreases.